2022
DOI: 10.1371/journal.pone.0263595
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators and outcomes of hospitalised COVID-19 patients with neurological disease: An individual patient data meta-analysis

Abstract: Background Neurological COVID-19 disease has been reported widely, but published studies often lack information on neurological outcomes and prognostic risk factors. We aimed to describe the spectrum of neurological disease in hospitalised COVID-19 patients; characterise clinical outcomes; and investigate factors associated with a poor outcome. Methods We conducted an individual patient data (IPD) meta-analysis of hospitalised patients with neurological COVID-19 disease, using standard case definitions. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
1
22
0
2
Order By: Relevance
“…In particular, considering that it might be difficult to differentiate between the second and third scenarios, only patients who satisfied the criteria for COVID-19-related encephalitis/encephalopathies proposed in a recent individual patient data meta-analysis [ 15 ] were included in the “extensive inflammation or hypoxic brain injury within the context of encephalopathy” group. This allowed us to also include in the “unmasking of underlying still non-symptomatic PD” scenario only patients with no clinical or instrumental signs of extensive inflammation of the brain within the context of encephalitis/encephalopathies, particularly confirmed by the absence of brain MRI pathological changes.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, considering that it might be difficult to differentiate between the second and third scenarios, only patients who satisfied the criteria for COVID-19-related encephalitis/encephalopathies proposed in a recent individual patient data meta-analysis [ 15 ] were included in the “extensive inflammation or hypoxic brain injury within the context of encephalopathy” group. This allowed us to also include in the “unmasking of underlying still non-symptomatic PD” scenario only patients with no clinical or instrumental signs of extensive inflammation of the brain within the context of encephalitis/encephalopathies, particularly confirmed by the absence of brain MRI pathological changes.…”
Section: Methodsmentioning
confidence: 99%
“…A recent individual patient data meta-analysis of 1979 hospitalized patients with neurological COVID-19 from 83 studies showed that poor outcome corresponding to moderate-to-severe disability or death (mRS 3–6) was more common in patients with cerebrovascular events (76%), than encephalopathy (54%) [47].…”
Section: Complications and Outcomesmentioning
confidence: 99%
“…Although most of these severe manifestations have been reported in adult patients, few pediatric patients have such complications (Akın et al, 2021, Gaughan et al, 2021, Vraka et al, 2021. Based on a recent published meta-analysis the authors found that in patients with COVID-19-induced encephalopathy, age 70-79 years, low admission lymphocyte counts, and use of corticosteroid and anticoagulants are considered poor prognostic factors (Singh et al, 2022). On the other hand, data about the pediatric COVID-19-induced encephalopathy are scare, and most of the available data are based on case reports and few case series (Gaughan et al, 2021, McAbee et al, 2020.…”
Section: Several Neurological Involvements Have Previously Been Repor...mentioning
confidence: 99%
“…Although the primary target of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the respiratory system, neurological manifestations, including encephalopathy, have been reported in some patients (Akın et al, 2021, Lin et al, 2020, McAbee et al, 2020, Singh et al, 2022, Vraka et al, 2021. The first case of meningoencephalitis associated with SARS-CoV-2 infection was reported in an adult patient in March 2020, with a positive specific SARS-CoV-2 ribonucleic acid (RNA) in the cerebrospinal fluid (CSF) (Poyiadji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%